2022
DOI: 10.3389/fpsyg.2022.999111
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The COVID-19 fear, anxiety, and resilience among emergency nurses

Abstract: BackgroundBesides physical complications, COVID-19 is associated with psychological issues such as fear and anxiety. High resilience in nurses enables them to adopt positive coping mechanisms and successfully operate in the stressful environment of COVID-19 wards. The present study aimed to evaluate the correlation between COVID-19 fear and anxiety with resilience in the emergency nurses of the hospital affiliated with Kurdistan University of Medical Sciences (west of Iran) in 2021.Materials and methodsThis cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…It is a known phenomenon that working with Covid-19 patients is highly frightening and remains a matter of safety for nurses [ 13 , 14 ]. Other studies from India and around the world report similar findings on the fear and anxiety experienced by nurses during the Covid-19 pandemic [ 15 17 ]. This highlights the need for urgent attention and action.…”
Section: Discussionsupporting
confidence: 59%
“…It is a known phenomenon that working with Covid-19 patients is highly frightening and remains a matter of safety for nurses [ 13 , 14 ]. Other studies from India and around the world report similar findings on the fear and anxiety experienced by nurses during the Covid-19 pandemic [ 15 17 ]. This highlights the need for urgent attention and action.…”
Section: Discussionsupporting
confidence: 59%
“…This result is supported by Piotrowski et al [78] and Hudgins [79] who have found a positive relationship between resilience and job satisfaction. Moreover, this review and the literature [80][81][82][83][84] have found low levels of stress and fear to positively impact resilience.…”
Section: Intrapersonal Factorsmentioning
confidence: 84%
“…According to the results of this study, nurses had lower resilience levels in opposition to psychologists and physicians, which had the highest RSA score. Several studies 29,30 conducted with nurses showed also lower levels of resilience compared to other occupations. This may happen, since these professionals were in direct contact with patients and perform several functions, such as administering medication, performing vaccinations, performing physical examinations, and heavier workload due to working in shifts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nurses assumed a more active role in the COVID-19 pandemic, compared to other healthcare professionals, and their occupational balance was altered. 31 Also, the COVID-19 pandemic made nurses constantly fear contracting the virus and infecting their families, 30 a distress that is higher for healthcare workers in emergency services. 32 …”
Section: Discussionmentioning
confidence: 99%